1989
DOI: 10.1111/j.1600-0536.1989.tb04653.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergic contact sensitivity to quinophthalone

Abstract: A 73-year-old patient, diagnosed as having seborrheic dermatitis, was patch tested with his hair preparations. The hair stick gave a positive reaction. Among its ingredients, D & C Yellow No. 11, from 0.0001% to 0.1%, and perfume showed positive reactions. D & C Yellow No. 11 was found to consist only of quinophthalone by chemical analyses. The concentration of quinophthalone in the hair stick was determined as 9.41 ppm w/w by high-performance liquid chromatography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…One case with body wash specified MI/MCI as the allergen culprit. Thirteen studies with a total of 284 patients identified consumer and medical products, such as hair clips and headband (n = 3), wig adhesive (n = 2), wig (n = 2), continuous positive airway pressure (CPAP) machine strap (n = 2), hair stick (n = 1), spectacle frames (n = 1), aromatherapy (n = 1), leather hat (n = 1), and unspecified (n = 271) as causative scalp allergens 4,6,12,16,91–99 . Common positive patch tests were found for nickel in hair clips and headband, 2-ethylhexyl acrylate and 2-hydroxyethyl methacrylate in wig adhesives, and neoprene/dialkyl thioureas in CPAP straps.…”
Section: Resultsmentioning
confidence: 99%
“…One case with body wash specified MI/MCI as the allergen culprit. Thirteen studies with a total of 284 patients identified consumer and medical products, such as hair clips and headband (n = 3), wig adhesive (n = 2), wig (n = 2), continuous positive airway pressure (CPAP) machine strap (n = 2), hair stick (n = 1), spectacle frames (n = 1), aromatherapy (n = 1), leather hat (n = 1), and unspecified (n = 271) as causative scalp allergens 4,6,12,16,91–99 . Common positive patch tests were found for nickel in hair clips and headband, 2-ethylhexyl acrylate and 2-hydroxyethyl methacrylate in wig adhesives, and neoprene/dialkyl thioureas in CPAP straps.…”
Section: Resultsmentioning
confidence: 99%
“…1 Given the prevalence of documented cases of misdiagnosed or underdiagnosed scalp ACD, it is crucial to accurately differentiate scalp ACD from other conditions. 25,26 Trichoscopy, or dermoscopy of the scalp, is often useful in helping distinguish between inflammatory scalp lesions. Scalp ACD trichoscopy can reveal dotted and comma vessels, simple loops, thin and thick arborizing vessels, white scales, simple red loops, yellow exudate, and generalized erythema.…”
Section: Clinical Presentation and Differential Diagnosismentioning
confidence: 99%
“… 1 Given the prevalence of documented cases of misdiagnosed or underdiagnosed scalp ACD, it is crucial to accurately differentiate scalp ACD from other conditions. 25 , 26 …”
Section: Clinical Presentation and Differential Diagnosismentioning
confidence: 99%